Effective solvent-free oxidation of cyclohexene to allylic products with oxygen by mesoporous etched halloysite nanotube supported Co2+. Issue 27 (19th April 2018) - Li, Cuiping; Zhao, Yue; Zhu, Tianwen; Li, Yan'ge; Ruan, Jiajia; Li, Guanghui
Abstract : Mesoporous eHA@Co 2+ nanorods with effective solvent-free oxidation of cyclohexene to allylic products with O2 have been successfully fabricated by HCl selective etching of Al2 O3 from halloysite nanotubes and the impregnation method consecutively. Abstract : One dimensional mesoporous etched halloysite nanotube supported Co 2+ is achieved by selective etching of Al2 O3 from halloysite nanotube (HA) and immersing the etched HA (eHA) into the Co(NO3 )2 ·6H2 O solution consecutively. By facilely tuning the etching time and the weight ratio of Co(NO3 )2 ·6H2 O to eHA, the morphology, specific surface area and the supported Co 2+ content of the mesoporous material can be tuned. The method for mesoporous material is scaled up and can be extended to other clay minerals. The mesoporous eHA supported Co 2+ is used as catalyst for the selective catalytic oxidation of cyclohexene in solvent-free reaction system with O2 as oxidant. The results shows the catalytic activity is dependent on etching time, weight ratio of Co(NO3 )2 ·6H2 O to eHA, calcination treatment and reaction time/temperature. Among them, mesoporous eHA supported Co 2+ prepared with 18 h etching time and 2 : 1 Co(NO3 )2 ·6H2 O/eHA weight ratio without calcination (HA/HCl-18 h/Co 2+ -2 : 1) demonstrates the highest catalytic activity under 75 °C reaction temperature and 18 h reaction time (58.30% conversion and 94.03% selectivity to allylic products). Furthermore, HA/HCl-18 h/Co 2+ -2 : 1 has exhibit superior cycling stability with 37.69% conversion and 92.73% selectivity to allylic products after three cycles.